SINERGI MASYARAKAT DAN TENAGA KESEHATAN DALAM VAKSINASI JAPANESE ENCHEPHALITIS (JE) DI WILAYAH PUSKESMAS NGAGLIK II - Tri Susilani, Amalina; Ratnaningsih, Dwi; Restu Yuliastri, Tita (Permata Indonesia, 2025)
Japanese Encephalitis (JE) is a viral infectious disease that can attack the central nervous system and cause serious complications, especially in children. As part of efforts to prevent infectious diseases, the Ngaglik Health Center together with the D III Midwifery Study Program of the Permata Indonesia Health Polytechnic Yogyakarta and the community carried out JE vaccination activities. This community service aims to support the success of vaccination through a collaborative approach between health workers, cadres, and community leaders. Activities are carried out through socialization, education, technical assistance, and monitoring of vaccination implementation. The results showed high community participation, increased knowledge of cadres, and vaccination coverage that exceeded the target. This synergy is an effective model in strengthening immunization efforts in the health center's work area